ANALYSE DE LA RÉGÉNÉRATION SPONTANÉE DE LA VÉGÉTATION POST-INCENDIE DANS LA FORET DE DAR CHICHOU (CAP BON, TUNISIE NORD-ORIENTALE) - KHALED ABAZA (Revue Roumaine de Géographie)
The assessment of spontaneous regeneration of post-fire forest vegetation in Dar Chichou Forest (Cape Bon, North-East of Tunis). This paper examines the impact of fires on semiarid Mediterranean forests. From July 14 to July 20, 2011, the vast forest of Dar Chichou, located in the northern end of the Cap Bon peninsula, suffered very serious damage of more than 400 hectares of natural and artificial vegetation. Based on several observations and fieldwork measurements conducted between September 2011 and September 2014, this study assesses the impact of various disturbances caused by the July 2011 fires biodiversity in a Tunisian context, where the forest, in addition to climatic and ecological conditions that trigger fires, has been experiencing a very strong human pressure. In addition to the almost total carbonization of the fauna and flora of the devastated area observed the day after the outbreak of the disaster, the study highlights a good natural regeneration of vegetation, in particular broadleaf trees and secondary vegetation, but according to very varied rhythms and aspects.